The construction of a nomogram to predict the prognosis and recurrence risks of UPJO - Ma, Wenyue; Gao, Hongjie; Chang, Mengmeng; Lu, Zhiyi; Li, Ding; Ding, Chen; Bi, Dan; Sun, Fengyin (Frontiers in Pediatrics, 2024)
Objective: This study was conducted to explore the risk factors for the prognosis and recurrence of ureteropelvic junction obstruction (UPJO). Methods:The correlation of these variables with the prognosis and recurrence risks was analyzed by binary and multivariate logistic regression. Besides, a nomogram was constructed based on the multivariate logistic regression calculation. After the model was verified by the C-statistic, the ROC curve was plotted to evaluate the sensitivity of the model. Finally, the DCA)was conducted to estimate the clinical benefits and losses of intervention measures under a series of risk thresholds. Results: Preoperative automated peritoneal dialysis (APD), preoperative urinary tract infection (UTI), preoperative renal parenchymal thickness (RPT), Mayo adhesive probability (MAP) score, and surgeon proficiency were the high-risk factors for the prognosis and recurrence of UPJO. In addition, a nomogram was constructed based on the above 5 variables. The area under the curve (AUC) was 0.8831 after self cross-validation, which validated that the specificity of the model was favorable.The column chart constructed by five factors has good predictive ability for the prognosis and recurrence of UPJO, which may provide more reasonable guidance for the clinical diagnosis and treatment of this disease.